Literasi Media Internet di Kalangan Mahasiswa - Adiarsi, Gracia Rachmi; Stellarosa, Yolanda; Silaban, Martha Warta (Humaniora, 2015)
This study aims to find out to what extent the Internet users in line with media literacy. According to Indonesia Internet Service Provider Association (APJII) and BPS Statistic Indonesia, it was found that Internet users in Indonesia have grown since three years ago up to 13% or become 71.19 million people until the end of 2013. According to research survey MarkPlus Insight, ?netizen? or Internet users who spend more than three hours per day on Internet. Moreover, they are increasing from 24,2 Million people in 2012 and become 31,7 million people in 2013. This research used qualitative method by gathering the data through Focus Group Discussion (FGD) to private university students who spent for Internet 5 hours per day and less than 5 hours per day. The theory used in this research was media literacy. The result of this research stated that students who accessed the Internet below 5 hours per day were already busy with work and not too intense in using the Internet either via smartphone or a computer. Different findings came up from the students who accessed the Internet over 5 hours per day. Most of the time, they used the Internet for social media and instant messaging (instant messenger) through smartphones. Critical attitude towards the media message depends on the informants? interest toward the information.